Temporary help agencies and the advancement prospects of low earners - Fredrik Andersson; Harry J. Holzer; Julia Lane (Institute for the Study of Labor (IZA), 2007)
In this paper we use a very large matched database on firms and employees to analyze the use of temporary agencies by low earners, and to estimate the impact of temp employment on subsequent employment outcomes for these workers. Our results show that, while temp workers have lower earnings than others while working at these agencies, their subsequent earnings are often higher but only if they manage to gain stable work with other employers. Furthermore, the positive effects seem mostly to occur because those working for temp agencies subsequently gain access to higher-wage firms than do comparable low earners who do not work for temps. The positive effects we find seem to persist for up to six years beyond the period during which the temp employment occurred.
Keywords: 330; Temp; employment; advancement; intermediaries; Leiharbeit; Dualer Arbeitsmarkt; Arbeitsmobilität; Arbeitsvertrag; Lohnniveau; USA